REPRESENTASI KARTUN EDITORIAL JAWA POS BERTEMA KLAIM MALAYSIA TERHADAP WILAYAH DAN HASIL BUDAYA INDONESIA - Cons. Tri Hadoko (Jurnal Dimensi Seni Rupa dan Desain, 2010)
Abstract The Jawa Post editorial cartoons which appointed Malaysia claimed on Indonesia's teritority and cultural products in this article discussed about Ambalat sea and Indonesia's cultural products which was claimed by Malaysia. Editorial cartoon analisist metode adapted Cartoon analysis Worksheet which was designed by the Education Staff, National Archieves and Records Administration , Washington DC. The analisist clue explained that editorial cartoons described Mlaysia as the guilty side and formalized opinion that Malaysia was thief. then rise term Malingsia not Malaysia anymore, maling mean thief. Those editorial cartoons described asweel Indonesia nation was week nation, not concerned to their national treasure and cultural products, fulfilled by social and economic problems also political intricts which effected inside emasculation. Those made another nation easy to infiltrated, intervantions, agitated Indonesia stability AbstrakKartun editorial jawa Pos yang mengangkat tema kalin Malaysia terhadap wilayah dan hasil buudaya Indoensia dalam tulisan ini membahas tentang laut Ambalat dan klaim hasil budaya Indoensia seperti tari pendet, reog ponorogo , batik, lagi rasa sayange dan sebagainya oleh Malaysia. Metode analisis kartun editorial mengadaptasi Cartoon Analysis Worksheet yang didesain dan dikembangkan oleh The Education Staff, National Archieves and Records Administration, Washington DC. Hasil analisis mengungkapkan bahwa kartu editorial menggam,barkan malaysia sebagai pihak yang bersalah dan membentuk opini bahwa Malaysia adalah pencuri, sehingga muncullah istilah Malingsia bukan lagi Malaysai, maling artinya pencuri